Enhancement of the Solubility and Dissolution Profile of Rivaroxaban by the Antisolvent Precipitation Technique: A Promising Approach - Benga, Claudia Maria; Ozon, Emma Adriana; Musuc, Adina Magdalena; Anuța, Valentina; Sârbu, Iulian; Surdu, Vasile Adrian; Teodorescu, Florina; Rusu, Adriana; Popa, Lăcrămioara; Ghica, Mihaela Violeta; Chandak, Abhay; Pîrvu, Cristina Elena Dinu (MDPI AG, 2026)
The development of new pharmaceutical forms with high solubility and enhanced bioavailability currently represents a significant challenge in the pharmaceutical industry. Currently, methods are still being explored to improve the oral bioavailability of Rivaroxaban, estimated to be 60%, due to its low solubility. To address these challenges, this study uses the antisolvent precipitation method to obtain three nanosuspensions of rivaroxaban (RIV), using Poloxamer 188 (P188) and hydroxypropyl methylcellulose (HPMC) by varying their concentrations (1:1:1, 1:1:2, and 1:2:1 molar ratios). The RIV nanosuspensions were characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). The antisolvent precipitation method led to the successful formulation of the three RIV nanosuspensions. Afterward, the formulated tablets containing dry RIV nanosuspensions were pharmaceutically characterized. RIV-P188-HPMC (1:1:1) and RIV-P188-HPMC (1:2:1) dry nanosuspensions demonstrated a uniform flow, and they were subsequently analyzed to establish the in vitro dissolution profile. The nanosuspension formulation with a higher content of P188 showed superior performance. Overall‚ the results of this study show that the antisolvent precipitation method in the presence of different amounts of HPMC and P188 is very efficient in increasing the dissolution rate of rivaroxaban to achieve its better efficiency.
Keywords: rivaroxaban; antisolvent precipitation; oral bioavailability; nanosuspensions; dissolution profile; Poloxamer 188